2022
DOI: 10.1101/2022.11.26.517939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

scRNAseq of healthy and irradiated mouse parotid glands highlights crosstalk between immune and secretory cells during chronic injury

Abstract: Translational frameworks to understand the chronic loss of salivary dysfunction that follows after clinical irradiation, and the development of regenerative therapies remain an unmet clinical need. Understanding the transcriptional landscape long after irradiation treatment that results in chronic salivary hypofunction will help identify injury mechanisms and develop regenerative therapies to address this need. Advances in single cell (sc)RNAseq have made it possible to identify previously uncharacterized cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Interestingly, a study utilizing single cell RNA sequencing (scRNAseq) found that fractionated IR resulted in a significant increase in DPT cells at 10 months following treatment, and further, reported that DPT cells had the highest number of radiation-induced differentially expressed genes (73). This paper also reported substantial immune-epithelial cell interactions, specifically increased signaling from acinar to DPT and CD8+ T cells.…”
mentioning
confidence: 81%
“…Interestingly, a study utilizing single cell RNA sequencing (scRNAseq) found that fractionated IR resulted in a significant increase in DPT cells at 10 months following treatment, and further, reported that DPT cells had the highest number of radiation-induced differentially expressed genes (73). This paper also reported substantial immune-epithelial cell interactions, specifically increased signaling from acinar to DPT and CD8+ T cells.…”
mentioning
confidence: 81%
“…In addition, this Tfrc hi cluster expressed higher levels of Nktr, which is also found in the kidney and colon epithelium (Human Protein Atlas, www.proteinatlas.org), of the extracellular component Fgg (fibrinogen), of the transporter for long-chain fatty acids Slc27a2, and of the long noncoding RNA (lncR-NAs) Gm26917 that promotes the survival of satellite cells [64]. Recently, a putative acinar precursor characterized by high expression of Etv1, Neat1, and Gm26917 was identified in irradiated parotid glands [65]. Together with a relatively low RNA content (Figure S6A), the Tfrc hi cluster might correspond to cells with minimal secretory function, which could suggest incomplete differentiation or a functionally quiescent state.…”
Section: Characterization Of Lg Epithelial-cell Clustersmentioning
confidence: 99%